A giant γ-ray flare from the magnetar SGR 1806–20 - Palmer, D. M.; Barthelmy, S.; Gehrels, N.; Kippen, R. M.; Cayton, T.; Kouveliotou, C.; Eichler, D.; Wijers, R. A. M. J.; Woods, P. M.; Granot, J.; Lyubarsky, Y. E.; Ramirez-Ruiz, E.; et al. (Nature (London), 2005)
Flares back in fashion On 27 December last year, SGR1806–20, a soft γ-ray repeater in Sagittarius, released a giant flare that has been called the brightest explosion ever recorded. SGRs are X-ray stars that sporadically emit low-energy γ-ray bursts. They are thought to be magnetars: neutron stars with observable emissions powered by magnetic dissipation. Five papers in this issue report initial and follow-up observations of this event. The data are remarkable: for instance in a fifth of a second, the flare released as much energy as the Sun radiates in a quarter of a million years. Such power can be explained by catastrophic global crust failure and magnetic reconnection on a magnetar. Releasing a hundred times the energy of the only two previous SGR giant flares, this may have been a once-in-a-lifetime event for astronomers, and for the star itself. Two classes of rotating neutron stars—soft γ-ray repeaters (SGRs) and anomalous X-ray pulsars—are magnetars 1 , whose X-ray emission is powered by a very strong magnetic field ( B ≈ 10 15 G). SGRs occasionally become ‘active’, producing many short X-ray bursts. Extremely rarely, an SGR emits a giant flare with a total energy about a thousand times higher than in a typical burst 2 , 3 , 4 . Here we report that SGR 1806–20 emitted a giant flare on 27 December 2004. The total (isotropic) flare energy is 2 × 10 46 erg, which is about a hundred times higher than the other two previously observed giant flares. The energy release probably occurred during a catastrophic reconfiguration of the neutron star's magnetic field. If the event had occurred at a larger distance, but within 40 megaparsecs, it would have resembled a short, hard γ-ray burst, suggesting that flares from extragalactic SGRs may form a subclass of such bursts.